Problematika Mahasiswa Calon Guru Dalam Pelaksanaan Pembelajaran Micro Teaching di STIQ Amuntai - Fitriani; Jatul; Siti Zulpa Zahra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
From previous research, during the implementation of micro teaching students often experience several problems, such as lack of mastery of learning materials, difficulties in making lesson plans, inconsistent duration of time, feelings of pressure, low self-confidence and lack of teaching motivation. These problems resulted in the results of student practice being less than optimal. Based on the existing problems, researchers are interested in conducting further research related to the problems experienced by students when practicing micro teaching at STIQ Amuntai. The purpose of this study was to identify the problems that occurred to students in the implementation of micro teaching at the Amuntai College of Al-Quran Science (STIQ). The method used in this research is a qualitative method with a descriptive approach. The data collection techniques in this study used observation techniques, online interviews using google forms and documentation of STIQ Amuntai students. The results showed that there were several problems faced by students when practicing micro teaching, including lack of confidence, difficulty in speaking Indonesian, difficulty in determining strategies or methods, difficulties in conveying learning objectives, difficulties in choosing and using media, difficulties in apperception, difficulties in explaining. materials, and difficulties in making lesson plans.